CMV retinitis in a stem cell transplant recipient treated with foscarnet intravitreal injection and CMV specific immunoglobulins. (December 2020) - Vassallo, Francesco; Nuzzi, Raffaele; Cattani, Ilaria; Dellacasa, Chiara; Giaccone, Luisa; De Rosa, Francesco Giuseppe; Cavallo, Rossana; Iovino, Giorgia; Brunello, Lucia; Bruno, Benedetto; Busca, Alessandro
Cytomegalovirus (CMV) retinitis (CMVR) has been reported rarely in patients undergoing allogeneic hematopoietic stem cell transplantation (HSCT). In addition, little is known about strategies for ophthalmic surveillance and adequate antiviral treatment of CMVR. A case of CMVR in an allogeneic HSCT recipient is described, including clinical signs and therapy. An adult patient received HSCT from a matched unrelated donor for treatment of a Burkitt lymphoma. Donor and recipients were both CMV positive. Starting on day +40, the patient presented multiple CMV reactivation, treated with valganciclovir, foscarnet and a combination of both. On day +160, the patient started complaining of conjunctival hyperaemia and a decrease in visual acuity. Fundoscopy revealed retinal lesions consistent with CMVR, although whole blood CMV DNAemia was negative. Aqueous humor biopsy showed the presence of CMV infection (CMV DNA 230400 UI/ml). CMVR was treated with foscarnet (180 mg i.v. and 1.2 mg intravitreal injection) combined with anti CMV immunoglobulin at 0.5 ml/kg every 2 weeks. After 4 weeks of systemic therapy, 20 weekly doses of intravitreal foscarnet and six cycles of immunoglobulins, a significant improvement of visual acuity was observed. The treatment was well tolerated with no side effect. In conclusion, our case suggests that systemic and local antiviral treatment combined with CMV-specific-IVIG, may reduce CMV load in the eye of patients with CMVR, leading to a consistent improvement of visual acuity. Systematic ophthalmologic examination should be recommended in HSCT recipients with multiple CMV reactivations and high peak CMV DNA levels.